The consequences of viral infection on protists - Queiroz, Victoria Fulgencio; Tatara, Juliana Miranda; Botelho, Bruna Barbosa; Rodrigues, Rodrigo Araújo Lima; Almeida, Gabriel Magno de Freitas; Abrahao, Jonatas Santos (Communications biology, 2024)
Protists encompass a vast widely distributed group of organisms, surpassing the diversity observed in metazoans. Their diverse ecological niches and life forms are intriguing characteristics that render them valuable subjects for in-depth cell biology studies. Throughout history, viruses have played a pivotal role in elucidating complex cellular processes, particularly in the context of cellular responses to viral infections. In this comprehensive review, we provide an overview of the cellular alterations that are triggered in specific hosts following different viral infections and explore intricate biological interactions observed in experimental conditions using different host-pathogen groups. An in-depth review compiling information about the effects of virus infections in protists and discussing how these interactions are important for cell biology, ecology and biotechnology.